LEARNING TO LEARN COMPETENCE IN THE CONTEXT OF ADULT EDUCATION - Staniulevičienė, Dalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The purpose of this article is to provide a description of learning to learn competence, highlighting the issue of abilities that are needed. The necessary abilities, as components of learning to learn competence, are characterized. In order to achieve the purpose, a theoretical frame is provided in this article. Also preliminary data of the quantitative pilot research presented. It is important to mention, that learning to learn is a process in which learning situations are reflectively analysed in an effort to understand oneself. Therefore, through learning to learn, the individual can identify his or her strengths and weaknesses, and thus use personally appropriate learning strategies. The model of learning to learn competence, constructed by the author of this article, is presented.